Evaluation of a multi-site health services psychology training program for telehealth and integrated behavioral health - McCord, Carly; Garney, Whitney; Garcia, Kristen; Macareno, Blanca; Williamson, Meredith (Frontiers in Psychology, 2024)
Introduction Training future providers in telehealth and integrated care models can improve access and outcomes, especially among rural and underserved populations. The (blinded) project implemented behavioral health training for health service psychology doctoral students with three partner organizations. Trainees received both experiential and didactic training in telehealth and integrated behavioral health. Telehealth was utilized for remote warm hand-offs, hybrid shared appointments, therapy sessions, coordination with providers, and supervision. Program elements included opportunities for consultations with experts in other disciplines, supportive mentorship, exposure to various parts of a healthcare system, and interactions with diverse clients. Methods The (blinded) training program evaluated trainee outcomes using fourteen interviews and three focus groups. Interviews and focus groups examined aspects of the program that contributed to trainees’ knowledge, skills, and attitudes. Results Evaluation results revealed increased levels of trainee confidence, autonomy and independence. Training reportedly enabled improved ability to collaborate and communicate with other professions, increased flexibility and adaptability, and openness to others’ ideas. Trainees reported the program’s use of telehealth enhanced awareness of their own skills and team members’ perspectives of technology in care delivery. Discussion Descriptions of the three care models, lessons learned, and qualitative results about trainee outcomes can be translated into best practices for workforce development and enhance psychology trainees’ self-awareness and ability to incorporate others’ viewpoints about technology and treatment approaches into healthcare.